Corpus Analysis for Language Studies at the University Level - Valūnaitė Oleskevičienė, Giedrė (Cambridge Scholars Publisher, 2021)
This book highlights corpora use in teaching foreign languages in university education. It will appeal to both academics and practitioners interested in the process of teaching foreign languages at more advanced levels while applying corpus analysis and building tools for corpus annotation. It provides a detailed case study of analyzing the terminology of constitutional law in both English and Lithuanian as an example to illustrate the possibility of integrating corpus analysis tools into the process of teaching foreign languages in university education. The book reveals that initial linguisti.